The glass cage : automation and us - Carr, Nicholas G., 1959- (W.W. Norton & Company, 2014)
In The Glass Cage, best-selling author Nicholas Carr digs behind the headlines about factory robots and self-driving cars, wearable computers and digitized medicine, as he explores the hidden costs of granting software dominion over our work and our leisure and reveals something we already suspect: shifting our attention to computer screens can leave us disengaged and discontented.